2014
DOI: 10.1080/00380768.2014.922407
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil properties and C dynamics to land-use change in the west of Loess Plateau

Abstract: Land-use change (LUC) is widely considered a major factor that affects soil organic carbon (SOC) sequestration. The impacts of four LUC types on soil properties, SOC, particulate organic carbon (POC) and labile organic carbon (LOC) at the 0-100 cm depth were examined in the west of Loess Plateau, northwest China. Bulk density at the 20-40 cm depth increased significantly after native grassland conversion to cropland, while artificial grassland establishment and abandonment on former cropland caused reverse cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Bulk density (BD) of the present study (0.62-0.83 g cm −3 ) is within the range reported by Baumler and Zech (1994) (0.6-1.8 g cm −3 ), and it increases with a decrease in soil depth in all the land-use types. Our results agree with the report of several other studies from different land-use types of the world (Zhang et al 2014;Francaviglia et al 2017). Higher soil bulk density in the inner soil layers is due to less organic matter and weight of the overlying horizons (Grüneberg et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Bulk density (BD) of the present study (0.62-0.83 g cm −3 ) is within the range reported by Baumler and Zech (1994) (0.6-1.8 g cm −3 ), and it increases with a decrease in soil depth in all the land-use types. Our results agree with the report of several other studies from different land-use types of the world (Zhang et al 2014;Francaviglia et al 2017). Higher soil bulk density in the inner soil layers is due to less organic matter and weight of the overlying horizons (Grüneberg et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the largest SOC sequestration rate for 80-and 100-year farmlands was possibly favored by the continuous increasing clay and silt content in surface soils. These results further demonstrated that fertilization in combination with irrigation activities can lead to surface soil C and N sequestration following the conversion of desert soil to farmland (Zhang et al 2014).…”
Section: The Changes In Soc and Tn Stocks Over 100 Years' Cultivationmentioning
confidence: 71%
“…Second, following the initial rapid decline, SOC would reach a new steady-state after about 50 years of cultivation, therefore resulting in a slower rate of SOC loss during the later years (Lal, 2004a). Krishna et al, (2018) Lihua Zhang et al, (2014) reported that the significant increases (31.83%) in the SOC concentrations were observed at AG compared with AL at a depth of 0-10 cm, with no significant effect at a depth of 10-100 cm [Fig. 12a].…”
Section: Introductionmentioning
confidence: 99%